2016
DOI: 10.2147/opth.s117403
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes of combined trabecular micro-bypass and phacoemulsification in a predominantly Hispanic patient population

Abstract: PurposeThe purpose of this study was to evaluate intraocular pressure (IOP) and topical ocular hypotensive medication burden at 12 months postoperatively in a predominantly Hispanic patient population with primary open-angle glaucoma each implanted with one trabecular micro-bypass stent during cataract surgery.MethodsThis was a retrospective, consecutive case series. The main objective was to assess reduction of IOP and/or medication burden in all eyes at the 12-month postoperative exam. A secondary objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Meanwhile, iStent technology has predominantly been used in cases of mild to moderate OAG, where it has demonstrated long-term effectiveness and excellent safety [ 3 6 , 9 20 ]. However, several recent reports have shown that the iStent may also be beneficial in cases of more advanced disease [ 7 , 8 , 31 – 33 ]. Given the difficulty of treating refractory disease, and the risk profile associated with more invasive traditional interventions, the present study offers insight into a novel minimally invasive treatment approach for these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, iStent technology has predominantly been used in cases of mild to moderate OAG, where it has demonstrated long-term effectiveness and excellent safety [ 3 6 , 9 20 ]. However, several recent reports have shown that the iStent may also be beneficial in cases of more advanced disease [ 7 , 8 , 31 – 33 ]. Given the difficulty of treating refractory disease, and the risk profile associated with more invasive traditional interventions, the present study offers insight into a novel minimally invasive treatment approach for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, for more severe OAG, including refractory cases, treatments have typically involved incisional glaucoma surgeries such as trabeculectomy or tube shunts, with attendant immediate and long-term risks of sequelae such as endophthalmitis, hypotony, bleb leaks, fibrosis, and bleb infections [ 21 30 ]. In more recent years, however, emerging literature has pointed to the potential utility of trabecular micro-bypass stents for these more advanced glaucoma cases [ 7 , 8 , 31 – 33 ]. Going one step further, some recent studies have examined the effect of simultaneously increasing two forms of outflow via two proven treatment modalities (conventional outflow via trabecular micro-bypass, and both uveoscleral and conventional outflow via a prostaglandin analogue) [ 15 , 20 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, this device has amassed a sizable longterm evidence base regarding its safety and performance in eyes with open-angle glaucoma, in settings both with and without cataract surgery. Most studies of the device have assessed outcomes in mild to moderate glaucoma [17][18][19][20][21][22][23][24][25][26][27], but other patient populations increasingly have been the subject of evaluation, such as pseudoexfoliative glaucoma, severe or refractory glaucoma, or newly diagnosed, treatment-naïve glaucoma [28][29][30][31][32][33]. Another growing and relevant area of investigation has been economics outcomes research [34][35][36][37][38][39], which consistently has shown favorable cost-effectiveness of the iStent in various healthcare models around the world.…”
Section: Introductionmentioning
confidence: 99%
“… 29 Differences in outcomes between single versus multiple iStents have also been investigated. 11 13 14 17 20 21 23 - 25 29 31 In general, most studies have focused on patients with early stages of primary OAG 11 14 - 16 21 22 27 - 29 32 …”
Section: Introductionmentioning
confidence: 99%